1970
DOI: 10.1063/1.1674040
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Recombination Emission of NO2

Abstract: Metastable resolved recombination, ionization and emission coefficients of impurity ions in thermal plasmas AIP Conf.The visible emission from electronically excited N02 has been studied both with thermal excitation in an electric oven and with recombination excitation from the nitric oxide-atomic oxygen reaction. In both cases the emission is continuous with weaker, diffuse bands superimposed. The correlation of these bands with N02 absorption bands has been extended. The thermal emission continuum begins nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(9 citation statements)
references
References 22 publications
(10 reference statements)
1
8
0
Order By: Relevance
“…The NO 2 radical likely plays an important role in RDX decomposition. The luminescence spectrum of excited NO 2 is very broad, almost forming a continuum. The peak of this continuum emission varies depending on the conditions under which the excited NO 2 was produced, and can vary from the visible (500−600 nm) to the near-infrared (1200 nm). ,,,, Because of the differences in the experimental conditions, our results are not directly comparable to these other studies. Temperature and pressure effects likely change the emission spectrum of NO 2 .…”
Section: Resultsmentioning
confidence: 57%
“…The NO 2 radical likely plays an important role in RDX decomposition. The luminescence spectrum of excited NO 2 is very broad, almost forming a continuum. The peak of this continuum emission varies depending on the conditions under which the excited NO 2 was produced, and can vary from the visible (500−600 nm) to the near-infrared (1200 nm). ,,,, Because of the differences in the experimental conditions, our results are not directly comparable to these other studies. Temperature and pressure effects likely change the emission spectrum of NO 2 .…”
Section: Resultsmentioning
confidence: 57%
“…Continuum radiation from sources other than H 2 and He 2 + can also arise from the photorecombination of electrons with Ar þ 2 (Ar þ 2 þ e À ! Ar à 2 þ hν) [164] and the chemi- [165]. However, Park et al [84] reported that in atmospheric-pressure discharges, the contribution of these continuum spectra on the emission spectrum can be considered negligible.…”
Section: Sources Other Than Free Electronsmentioning
confidence: 99%
“…[1986] measured a value of 79 tzs for heterogeneously formed NO•. Variations between the lifetimes of NO2 have been attributed to mixing of the 2B and 2B 2 states or explained in terms of one or more of these excited states being coupled to the high vibrational levels of the 2A1 ground state [Douglas, 1966;Paulsen et al, 1970;Adler-Golden, 1989], yielding a wide range of values. The common assumption for the lifetime is ---70 tzs The e-folding distance on orbiter surfaces had been measured to be 20 cm [ Yee and Dalgarno, 1983;Swenson et al, 1986b].…”
Section: Introductionmentioning
confidence: 99%